PHYTOCHEMICAL AND ANTIMICROBIAL ACTIVITY ANALYSIS OF SWERTIA CHIRAYITA AND ARTEMISIA ABSINTHIUM PLANT EXTRACTS - Afzal, A; Aftab, B; Siddique, J; Babar, S; Sohail, A; Yasir, M; Hanif, S (Biological and Clinical Sciences Research Journal, 2021)
The Swertia chirayita and Artemisia absinthium (Afsanteen) plants extracts were evaluated for phytochemicals and their antimicrobial activity against 3 bacteria and 2 fungal strains by using the disc diffusion technique. Phytochemical analysis showed the presence of tannins, flavonoids, saponins, and terpenoids in Swertia chirayita while in Artemisia absinthium only saponins, terpenoids were present. To a very small extent tannins were present in the ethanolic extract of Afsanteen. But both plant extracts gave negative results for the presence of cardiac glycosides. Antibacterial activity of Swertia chirayita and Afsanteen plant extracts were screened against 3 bacterial strains (E. coli, Bacillus subtilis, Pseudomonas syringola) and 2 fungal strains (Aspergillus niger and Fusarium Solani). Ampicillin was used as a standard drug for antibacterial and antifungal activity. Results showed that Afsanteen and chirayita extracts showed activity against bacterial strains except for chirayita n-hexane and ethanol extract for Bacillus subtilis and Chirayita n-hexane extract for Pseudomonas syringola. A maximum zone of inhibition was noticed for chirayita ethanol extract against Pseudomonas syringola. But both plant extracts showed zero activity against fungal strains except Chirayita acetone extract against Fusarium solani while chirayita ethanol extract against Aspergillus niger. Both extracts of plants gave concentration-dependent activity. It was concluded that the presence of antimicrobial activity for both plant extracts indicated that is due to the presence of phytochemical compounds.